GILZ restrains neutrophil activation by inhibiting the MAPK pathway. Issue 1 (29th October 2018) - Ricci, Erika; Ronchetti, Simona; Gabrielli, Elena; Pericolini, Eva; Gentili, Marco; Roselletti, Elena; Vecchiarelli, Anna; Riccardi, Carlo
Abstract: Glucocorticoid-induced leucine zipper (GILZ) exerts anti-inflammatory effects on the immune cells. However, less is known about GILZ function in neutrophils. We aimed to define the specific role of GILZ in basal neutrophil activity during an inflammatory response. GILZ knockdown resulted in a persistent activation state of neutrophils, as evidenced by increased phagocytosis, killing activity, and oxidative burst in GILZ-knockout (KO) neutrophils. This enhanced response caused severe disease in a dinitrobenzene sulfonic acid (DNBS)-induced colitis model, where GILZ-KO mice had prominent granulocytic infiltrate and excessive inflammatory state. We used a Candida albicans intraperitoneal infection model to unravel the intracellular pathways affected by GILZ expression in activated neutrophils. GILZ-KO neutrophils had stronger ability to clear the infectious agent than the wild-type (WT) neutrophils, and there was more activation of the NOX2 (NADPH oxidase 2) and p47 phox proteins, which are directly involved in oxidative burst. Similarly, the MAPK pathway components, that is, ERK and p38, which are involved in the oxidative burst pathway, were highly phosphorylated in GILZ-KO neutrophils. Evaluation of GILZ expression kinetics during C. albicans infection revealed down-regulation that correlated inversely with the state of neutrophil activation, which was evaluated as oxidative burst. Overall, our findings define GILZ as a regulator of neutrophil functions, as its expression contributes to limiting neutrophil activation by reducing the activation of the signaling pathways that control the basal neutrophil functions. Controlling GILZ expression could help regulate a continuous inflammatory state that can result in chronic inflammatory and autoimmune diseases. GILZ expression contributes to the inhibition of neutrophil activation by reducing MAPK pathway protein and NOX2 activity that control basal neutrophil functions.